Implementation of Reverse Logistics System in the Metal Industry Using Supply Chain Operation References (SCOR) Model with Analytical Hierarchy Process (AHP) Method - Pulansari, Farida; Nugraha, Isna; Winursito, Yekti Condro (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
As a result of the physical characteristics of metals and their use on a large scale, the industry producing metal products is one of the most important in terms of volume when implementing reverse logistics practices. The relationship between suppliers and customers from the perspective of environmental demands, companies using metal materials are mapped into the Supply Chain operation Reference (SCOR) model. In this study there are Key Performance indicators (KPIs) which are categorized based on the performance attributes of SCOR, namely reliability, responsiveness, agility, cost, and assets management. Using the Analytical Hierarchy Process (AHP) method is an analytical method for the structure of a problem and is used to make decisions on an alternative that is useful for solving complex unstructured problems. The result of this research is that the performance value obtained is a yellow traffic light which means that the application of reverse logistics metal at PT. XYZ has not been implemented properly, so further research must be carried out with primary data in the form of a reverse logistics process each step by step.